The THE EFFECT OF CAREER DEVELOPMENT, COMPENSATION AND ORGANIZATIONAL COMMUNICATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN MILLENIAL EMPLOYEES IN PT RAJAWALI NUSINDO - Suryaman, Donna Wibiananda; Bayudhirgantara, Michael (Dinasti Publisher, 2020)
This research aims to determine the influence of career development, compensation, and organizational communication of organization citizenship behavior of the millennial employee at PT Rajawali Nusindo. The methods used in this research use quantitative research methods. The samples used in this study were as much as 87 employees. Primary Data at can be from with questionnaires and interviews. Hypothesis in the test using regression analysis using SPSS 23. The study uses non probability sampling methods with random sampling techniques and the analysis method used is a double linear regression analysis. The results of this study show that career development has a significant positive influence over the organization citizenship behavior, significant positive compensation against organization citizenship behavior, organizational communication significantly positive to the organization citizenship behavior and simultaneously career development, compensation and communication of significantly affect the organization citizenship behavior. Keywords: Career Development, Compensation, Organizational Communications, Organization Citizenship Behavior (OCB).